2018
DOI: 10.1016/j.nbd.2018.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen synthase kinase-3β inhibition enhances myelination in preterm newborns with intraventricular hemorrhage, but not recombinant Wnt3A

Abstract: Intraventricular hemorrhage (IVH) in preterm infants results in reduced proliferation and maturation of oligodendrocyte progenitor cells (OPCs), and survivors exhibit reduced myelination and neurological deficits. Wnt signaling regulates OPC maturation and myelination in a context dependent manner. Herein, we hypothesized that the occurrence of IVH would downregulate Wnt signaling, and that activating Wnt signaling by GSK-3β inhibition or Wnt3A recombinant human protein (rh-Wnt3A) treatment might promote matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 62 publications
(98 reference statements)
2
13
1
Order By: Relevance
“…WNT/β-catenin/Tcf4 signaling pathway has been implicated in OPCs maturation and differentiation (21,67,70). In general, β-catenin does not accumulate in the cytoplasm under normal physiological condition because an existing complex consisting of AXIN2, APC, PP2A, GSK3, CK1α, could phosphorylate β-catenin (44).…”
Section: Discussionmentioning
confidence: 99%
“…WNT/β-catenin/Tcf4 signaling pathway has been implicated in OPCs maturation and differentiation (21,67,70). In general, β-catenin does not accumulate in the cytoplasm under normal physiological condition because an existing complex consisting of AXIN2, APC, PP2A, GSK3, CK1α, could phosphorylate β-catenin (44).…”
Section: Discussionmentioning
confidence: 99%
“… Microglia cell density was assessed using Iba‐1 specific antibody (catalog # AB5076, Abcam, Cambridge, U.K., http://www.abcam.com) as we and others previously described. A blind cell count was performed by two investigators to determine the cell density using ImageJ software with grid. We counted four sections in each pup and 5–6 pups from each group.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, increased AICD levels can promote Gsk3β activity, thereby reducing the translocation of β-catenin to the nucleus, which may contribute to the suppression of the Wnt/β-catenin pathway [118]. Interestingly, a study in the field of intraventricular hemorrhage (IVH), a common neurological complication of prematurity causing cognitive deficits and ID [119], which is accompanied by inhibited proliferation/maturation of OPCs and hypomyelination [120], demonstrated that Gsk3β activity interfered with OPC differentiation and myelination [121]. Furthermore, a cross-talk of Gsk3β and Notch signaling was shown, as inhibition of Gsk3β downregulated Notch signaling.…”
Section: App-mediated Signalingmentioning
confidence: 99%